2009
DOI: 10.1380/ejssnt.2009.568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pentacene Organic Field Effect Transistors by a Wet Process and their Carrier Mobilities

Abstract: Dewetting-induced crystallization from hot trichlorobenzene solutions led to the formation of aligned pentacene microfibers or plates, depending on preparation conditions. Fibers with a length of several hundred micrometer and a width of less than one micrometer can be prepared. Bottom-contact field effect transistors with fibers that were oriented perpendicular to the source and drain electrodes showed carrier mobilities as high as 0.04 cm 2 /Vs. In comparison, plate-like pentacene gave corrected mobilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The charge carrier mobility in crystalline fibers made of pentacene [18] is in the range of 0.1 -1 cm 2 V -1 s -1 [19] which is in the same range as the values reported by others for bottom contact field effect transistors (FETs) [20,21].…”
Section: Electronic and Photonics Applicationssupporting
confidence: 85%
See 1 more Smart Citation
“…The charge carrier mobility in crystalline fibers made of pentacene [18] is in the range of 0.1 -1 cm 2 V -1 s -1 [19] which is in the same range as the values reported by others for bottom contact field effect transistors (FETs) [20,21].…”
Section: Electronic and Photonics Applicationssupporting
confidence: 85%
“…Glass and silicon substrates were cleaned by sonication in alcoholic potassium hydroxide solution, followed by rinsing with water and acetone. The used roller apparatus was described in detail earlier [18,19]. Gold microelectrode patterns were prepared in-house by a lift-off technique.…”
Section: Methodsmentioning
confidence: 99%
“…We found that coating an electrode array with a pentacene solution resulted in fiber arrays between source and drain electrodes with charge carrier mobilities of up to 1.6cm 2 V 1 s 1 . 5 In summary, we have shown the potential usefulness of liquid processing of organic materials in patterning the active ingredients of photonic and electronic devices. OLEDs, microlenses, and transistors may just be the beginning.…”
mentioning
confidence: 91%